Comparative Analysis of Geospatial Survey Technologies for Engineering Project Efficiency and Accuracy - Tsering Wangchuk; Sonam Dorji Sonam Dorji (Techne: Journal of Engineering, Technology and Industrial Applications, 2025)
The increasing complexity of engineering and industrial projects demands geospatial survey technologies that are not only accurate but also efficient in terms of time and operational resources. Total Station, GNSS Real-Time Kinematic (RTK), and Unmanned Aerial Vehicle (UAV) photogrammetry are widely adopted in contemporary engineering practices, yet their comparative performance characteristics remain context-dependent. This study aims to conduct a quantitative comparative analysis of these three geospatial survey technologies by evaluating positional accuracy, survey duration, and spatial coverage within engineering project environments. A comparative research design was applied using secondary and simulated field data derived from engineering survey scenarios. The analysis reveals distinct trade-offs between measurement precision and operational efficiency across technologies. Total Station demonstrates superior accuracy for localized measurements, GNSS RTK offers balanced performance for control point establishment, while UAV photogrammetry excels in rapid large-area data acquisition. The findings contribute to engineering decision-making by providing empirical guidance on technology selection based on project scale and accuracy requirements.